2013
DOI: 10.1118/1.4789482
|View full text |Cite
|
Sign up to set email alerts
|

Temporal signal stability of KCl:Eu2+ storage phosphor dosimeters

Abstract: Purpose: Current KCl:Eu 2+ prototype dosimeters require a wait time of 12 h between irradiation and dosimetric readout. Although irradiating the dosimeters in the evening and reading on the following day works well in the clinical schedule, reducing the wait time to few hours is desirable. The purposes of this work are to determine the origin of the unstable charge-storage centers and to determine if these centers respond to optical or thermal excitation prior to dosimetric readout. Methods: Pellet-style KCl:E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…2 show that KCl:Eu 2+ detectors can be available for readout within 24 h because the fading behavior is stable within several hours postirradiation. (Note: In previous work, 22 we have shown that, for 0.05% Eu samples, a 15 min thermal treatment at 70 • C in air eliminates the fast fading component and renders the detector available for readout in less than 1 h.) Further, the results of Fig. 2 have important implications for future manufacturing challenges.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…2 show that KCl:Eu 2+ detectors can be available for readout within 24 h because the fading behavior is stable within several hours postirradiation. (Note: In previous work, 22 we have shown that, for 0.05% Eu samples, a 15 min thermal treatment at 70 • C in air eliminates the fast fading component and renders the detector available for readout in less than 1 h.) Further, the results of Fig. 2 have important implications for future manufacturing challenges.…”
Section: Discussionmentioning
confidence: 85%
“…After 12 h, the PSL intensity continues to decrease; however, the rate of decrease is much slower (referred to as the slow fading component). According to Xiao et al, 22 V k centers (a dihalide ion with a trapped hole) are mobile and can become stabilized by forming a complex with an activator ion. These complexes will remain stable until photon stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that a short thermal treatment can result in a fast stabilization of the PSL signal (Xiao et al, 2013). Therefore, the second readout scheme involved a pre-readout thermal annealing step.…”
Section: Methodsmentioning
confidence: 99%
“…Charges remaining trapped after readout can be erased with a bright, broadband light and the material can then be reused. Readout entails optical detection of PSL and can be done quickly, repeatedly, and with temporal stability 29 in ambient laboratory conditions. 30 In addition to being nearly energy independent in proton fields, KCl:Eu 2+ dosimeters also respond linearly to proton dose, exhibit dose-rate independence, and show both high radiation hardness and dynamic range.…”
Section: Introductionmentioning
confidence: 99%
“…Charges remaining trapped after readout can be erased with a bright, broadband light and the material can then be reused. Readout entails optical detection of PSL and can be done quickly, repeatedly, and with temporal stability 29 in ambient laboratory conditions 30 …”
Section: Introductionmentioning
confidence: 99%